PENGARUH VARIASI TEKANAN DAN SUHU PADA PENGADUKAN SERBUK ALUMINIUM (Al), MAGNESIUM (Mg), DAN SENG (Zn) TERHADAP SIFAT MEKANIK LOGAM DENGAN METODE METALURGI SERBUK - Sultan Achmad Dodo; Mahadi S.T., M.T (Talenta Publisher, 2020)
The use of aluminum is often found The mechanical properties of aluminum that arelightweight and rust resistant are among the reasons aluminum is often used for certainraw materials. However, the mechanical properties of aluminum if the levels are pure willnot correspond to the intended use, because the hardness value is very small. Thereforealuminum to add mechanical properties need to be added to other alloy compounds. Thisresearch is focused on Magnesium (Mg and Zinc (Zn) compounds with levels of variation ofboth aluminum 95%, magnesium 2.5%, 2.5% zinc. tons and temperature 550 ° C (2)pressure 10 tons and temperature 570 ° C (3) pressure 12 tons and temperature 590 ° C.From each impact test, hardness and tensile variations of the third which has the highestvalue. From the picture above, it can be seen that the spread in the pressure andtemperature variations in each Metal Matrix Composite (MMC) specimen. there is novariation in the MMC microstructure.